Engaging traders in strengthening seed systems in Tanzania: key drivers for selling grains of improved varieties of sorghum, common beans and groundnuts - Ong’or, Dennis; Ochieng, Justus; Mwakatwila, Atupokile; Mutua, Mercy; Radegunda, Kessy; Kelemera, Sylvia; Aseete, Paul; Mwenda, Emmanuel; Kadege, Edith; Madeni, Joachim; Rubyogo, Jean Claude (Springer Science+Business Media, 2025)
Seed systems in sub-Saharan Africa face constant challenges such as limited access to quality seeds and low varietal turnover. Despite numerous efforts aimed at formalizing seed markets, informal seed systems still dominate with 97% of smallholder farmers sourcing seeds of sorghum, common beans and groundnuts through farm-saved seed and local grain markets. Traders are deeply embedded in these local markets and are better positioned in shaping the seed demand, particularly among smallholders who buy grains as seeds from informal outlets. However, in most cases traders remain disconnected from formal breeding and seed dissemination efforts, subsequently leaving a gap between the development of improved varieties and their adoption by farmers. This scenario perpetuates the use of old varieties that are well known to traders, limiting potential benefits from genetic gains. In this study, we examine the factors that could influence traders’ decisions to sell grains of improved varieties. Data from a structured survey of 976 traders in Tanzania is used. We find that traders with higher financial capacity, stable market access, and those having strong relationships with farmers through credit provision are more likely to sell grains of improved varieties. Similarly, we find positive associations with switching to improved varieties among traders facing business challenges, accessing information through channels other than social media, and traders selling grains as seeds at sowing. In contrast, traders engaged inthe sale of highly demanded varieties are less likely to switch to new and improved varieties. Therefore, to spur the uptake of improved varieties, strengthening trader-farmer linkages, integrating traders into structured procurement systems, and enhancing trader involvement in participatory variety selection to refine existing and preferred varieties without changing them altogether are recommended. Additionally, there is need to strengthen business modeling programs to make grain traders’ businesses bankable, expand information sharing and facilitate access to credit enabling them to adequately offer technical support to the farmers they source grains from.